(untitled) (Research, Society and Development, 2022)
Problem-Based Learning (PBL) is an active teaching methodology that is increasingly used. Although its steps are well known and the extensive literature on its use in the most diverse scenarios, technological tools have emerged as an alternative to increase the contact between the tutor and the students and between the students themselves. The aim of this study was to identify the main platforms developed for the application in the BPA method. An integrative literature review was carried out in the SciELO, LILACS and PubMed databases, as well as in the eduCAPES Products, Theses and Dissertations library and in the Brazilian Digital Library of Theses and Dissertations (BDTD) of the Brazilian Institute of Information in Science and Technology (IBICT), Google and Google Scholar. The descriptors: Problem-Based Learning and Mobile Applications were used. Thus, we selected the studies published in English, Portuguese, and Spanish, and that addressed the use of mobile applications as a tool for teaching through PBL, being identified 14 products, analyzed according to type, place of development and target audience. All of these were limited to the description of a prototype or the developed product, without validation studies. In conclusion, the studies identified through this review pointed to the need for the development of products that allow interaction and that are evaluated for usability, acceptance, and efficacy for teaching.